Effect of inflammation stimulation on energy and nutrient utilization in piglets selected for low and high residual feed intake. (17th June 2015) - Labussière, E.; Dubois, S.; Gilbert, H.; Thibault, J. N.; Le Floc'h, N.; Noblet, J.; van Milgen, J.
Abstract : Selection of animals for improved feed efficiency can affect sustainability of animal production because the most efficient animals may face difficulties coping with challenges. The objective of this study was to determine the effects of an inflammatory challenge (using an intravenous injection of complete Freund's adjuvant – CFA) in piglets from two lines of pigs divergently selected during the fattening period for a low (RFI−) or a high (RFI+) residual feed intake (RFI; difference between actual feed intake and theoretical feed requirements). Nitrogen and energy balances (including heat production – HP – and its components: activity-related HP – AHP, thermic effect of feeding, and resting HP) were measured individually in thirteen 20-kg BW castrated male piglets (six and seven from RFI+ and RFI− line, respectively) fed at the same level (1.72 MJ ME/kg BW 0.60 per day) from 3 days before to 3 days after CFA injection. Dynamics of dietary U- 13 C-glucose oxidation were estimated from measurements of 13 CO2 production on the day before and 3 days after the CFA injection. Oxidation of dietary nutrients and lipogenesis were calculated based on HP and O2 consumption and CO2 production. The data were analyzed as repeated measurements within piglets in a mixed model. Before CFA injection, RFI− piglets had a lower resting energy expenditure than RFI+ piglets, which tended to increase energy retention because of a higher energy retention as fat. The CFA injection did not affect feed intake from the day following CFA injection onwards but it increased energy retention ( P =0.04). Time to recover 50% of 13 C from dietary glucose as expired 13 CO2 was higher in RFI+ piglets before inducing inflammation but decreased after to the level of RFI− piglets ( P <0.01). Oxidation of U- 13 C-glucose tended to slightly increased in RFI− piglets and to decreased in RFI+ piglets ( P =0.10) because of CFA. Additionally, RFI− piglets had a lower respiratory quotient during the 1st day following the CFA injection whereas RFI+ piglets tended to have a higher respiratory quotient. In conclusion, selection for RFI during the fattening period also affected the energy metabolism of pigs during earlier stages of growth. The effects of CFA injection were moderated in both lines but the most efficient animals (RFI−) exhibited a marked re-orientation of nutrients only during the 1st day after CFA, and seemed to recover thereafter, whereas the less efficient piglets expressed a more prolonged alteration of their metabolism.